Surgical crown lengthening: A case report - Wilson; Martina Amalia; Brian Merchantara; Trimurni Abidin (Journal of Dentomaxillofacial Science, 2022)
Objective: The concept of tooth lengthening was first to introduce by D. W. Cohen in 1962. This procedure often employs some combination of tissue reduction of removal, osseous surgery, and/or orthodontic movement for tooth exposure. The amount of tooth structure exposed above the osseous crest should be around 4-5 mm to provide a stable dentogingival complex and biological width to permit proper tooth preparation and a good marginal seal with retention for both provisional and final restoration. The present case report shows a surgical crown lengthening procedure as a treatment on a vertical crown fracture on a 47-years old woman. Methods: A 47 years old woman come to periodontics department as referred by conservative dentistry department with a tooth fracture on the second upper right premolar. Intraoral examination shows a crown fracture reaches until under the cemento enamel junction area. Periapical radiograph shows non-hermetic obturation. No extra oral anomaly was found. The retreatment of the tooth was done by the conservative dentistry then the surgical crown lengthening was done after the retreatment and the final restoration was done 3 months post-operative. Results: Proper identification and analysis of the problem playing the main role to achieve a satisfying outcome. The position of the gingival tissue, alveolar bone height, and clinical crown length are the determinant factor for identifying the problem. The case discussed here were treated with a surgical crown lengthening as a purpose to avoid any violation to biological width that can have a various effect to the periodontium leading to gingival inflammation, loss of attachment and alveolar resorption Conclusion: There is a significant relationship between restorative dentistry and periodontal health. Predictable long-term successful restoration requires a good combination between the restorative principles and the correct management of the periodontal tissue.